CRISPR/Cas9 Genome Editing: Future Treatment of Duane Retraction Syndrome - Zulfikar, Muhammad Raihan; Renesteen, Editha; Wardhani, Bantari W.K. (UI Scholars Hub, 2022)
Duane Retraction Syndrome (DRS) is characterized by limited eye movement. One of its causes is a mutation in the CHN1, MAFB, or SALL4 gene. Nowadays, the treatment for DRS is limited to glasses, occlusion, and surgery. However, this treatment has not been able to cure the disease’s hereditary issue. Another strategy to be considered for the treatment is CRISPR/Cas9, a tool for performing gene editing with a wide range of applications, including treating genetic diseases. We made sgRNA as a first step in using CRISPR/Cas9 as a treatment for DRS in silico using the CCTop website. By computing sgRNA, conducting tests, and analyzing the results, CRISPR/Cas9 may repair genetic mutations. Currently, there are no reports on the use of CRISPR/Cas9 in DRS. Hence, this study would be very useful as a starting point for using CRISPR/Cas9 as a DRS treatment. However, it needs to be further proven through in vivo, in vitro, and clinical trials study.